Extending the potential of Polydimethylsiloxane microchips - lbáñez, Alfredo (2005)
The search for microchannel wall modifications of simple use, that provide the desired functionality while the nonspecific adsorption is reduced to a mínimum, has allowed the development of new wall coatings. Specifically, the study of modifications that will enable to create robust microfluidic devices for the direct analysis of complex samples in which no sample pretreatment is required, are becoming a very important field of research, since they will allow microfluidic devices to become the analytical tool of choice for pharmaceutical and bioanalytical research fields.